Diagrammatic scale for the quantification of black spot severity in papaya leaves (Acta Scientiarum. Agronomy, 2023)
Black spot (Asperisporium caricae) is one of the main foliar fungal diseases of papaya crops. This disease acts directly on leaves and fruits causing leaf area reduction and fruit deterioration. The quantification of diseases is a fundamental part of the disease management and control process; therefore, a scale is required to help quantify black spot disease. The objective of this work was to propose a standardized methodology to quantify black spot severity in papaya leaves. A scale was developed considering the maximum and minimum values of the disease in the field that included eight levels of severity: 0.1, 0.3, 0.6, 1.0, 2.3, 5.0, 10.0, and 20.0%. Without the aid of a scale the disease is often overestimated, with absolute errors of approximately 75%. When the scale was used, 100% of the evaluators showed improved accuracy and precision, and absolute error was reduced to the 10% range. The scale also provided good repeatability and high reproducibility. The use of the scale provided an improvement in the R2 values, with mean values of 93 and 92 in the second and third evaluations, respectively, demonstrating that the scale is useful for different aspects of the pathosystem of A. caricae, such as for determining the efficiency of fungicides, characterization of varietal resistance, construction of the disease progression curve, and estimation of damage.